2016
DOI: 10.1038/mi.2015.106
|View full text |Cite
|
Sign up to set email alerts
|

The IL-33 receptor (ST2) regulates early IL-13 production in fungus-induced allergic airway inflammation

Abstract: Allergic airway inflammation (AAI) in response to environmental antigens is an increasing medical problem, especially in the Western world. Type 2 interleukins (IL) are central in the pathological response but their importance and cellular source(s) often rely on the particular allergen. Here, we highlight the cellular sources and regulation of the prototypic type 2 cytokine, IL-13, during the establishment of AAI in a fungal infection model using Cryptococcus neoformans. IL-13 reporter mice revealed a rapid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 62 publications
2
44
0
Order By: Relevance
“…Interleukin‐33‐induced eotaxin‐2/CCL24 production has previously been investigated in mice, where IL‐33 was reported to polarize alveolar macrophages toward an alternatively activated phenotype that were able to produce high levels of eotaxin‐2/CCL24 (and TARC/CCL17) in vitro in response to IL‐33 stimulation together with IL‐13 . Eotaxin‐2/CCL24 expression has been described to be dependent on IL‐13, and we and others have previously shown that IL‐13 is produced by airway ILC2s in response to IL‐33 stimulation in vivo . It is possible that airway ILC2s are contributing to the expression of eotaxin‐2/CCL24 by producing IL‐13 in our model of IL‐33‐induced eosinophilia.…”
Section: Discussionmentioning
confidence: 86%
“…Interleukin‐33‐induced eotaxin‐2/CCL24 production has previously been investigated in mice, where IL‐33 was reported to polarize alveolar macrophages toward an alternatively activated phenotype that were able to produce high levels of eotaxin‐2/CCL24 (and TARC/CCL17) in vitro in response to IL‐33 stimulation together with IL‐13 . Eotaxin‐2/CCL24 expression has been described to be dependent on IL‐13, and we and others have previously shown that IL‐13 is produced by airway ILC2s in response to IL‐33 stimulation in vivo . It is possible that airway ILC2s are contributing to the expression of eotaxin‐2/CCL24 by producing IL‐13 in our model of IL‐33‐induced eosinophilia.…”
Section: Discussionmentioning
confidence: 86%
“…Leukocytes bearing IL-33R respond to this alarm and propagate a type-2 immune response. Sub-lethal infection of mice with Cryptococcus neoformans leads to allergic inflammation that is dependent on IL-33R [20]. Interestingly, IL-33 expression is restricted to type-2 alveolar cells in Cryptococcus infected lungs [21].…”
Section: Epithelial Cells Promote Allergic Diseasementioning
confidence: 99%
“…For instance, IL-33-producing ILC2 cells were shown to have a detrimental role in pulmonary immunity against C. neoformans [124] and in patients with severe asthma associated with fungal sensitization [125]. Similar detrimental roles of IL-13-producing ILC2s were demonstrated in a mouse model of C. neoformans -induced airway inflammation [126] and in patients with Aspergillus -mediated chronic sinusitis [127]. Interestingly, prostaglandin I2 can reduce the number of Th2-expressing ILC2 in the lung, such as IL-13 and IL-5, and could potentially be exploited as a therapeutic strategy in this context [128].…”
Section: Innate Lymphocytesmentioning
confidence: 67%